Der Koheletkommentar des Hieronymus Einleitung, revidierter Text, Übersetzung und Kommentierung - Birnbaum, Elisabeth; Birnbaum, Elisabeth (Corpus Scriptorum Ecclesiasticorum Latinorum, 2014)
With his Commentary on Ecclesiastes, Hieronymus became the most influential interpreter of this Biblical book until the early modern era. For the first time, this volume offers a German translation and continuous commentary on Hieronymus's interpretations from the perspective of biblical scholarship. An extensive introduction to the topic and a revised Latin text complete the volume.